Integral of (x^2+y)+(2x-y) dy
The solution
Detail solution
-
Integrate term-by-term:
-
Integrate term-by-term:
-
The integral of a constant is the constant times the variable of integration:
∫2xdy=2xy
-
The integral of a constant times a function is the constant times the integral of the function:
∫(−y)dy=−∫ydy
-
The integral of yn is n+1yn+1 when n=−1:
∫ydy=2y2
So, the result is: −2y2
The result is: 2xy−2y2
-
Integrate term-by-term:
-
The integral of a constant is the constant times the variable of integration:
∫x2dy=x2y
-
The integral of yn is n+1yn+1 when n=−1:
∫ydy=2y2
The result is: x2y+2y2
The result is: x2y+2xy
-
Now simplify:
xy(x+2)
-
Add the constant of integration:
xy(x+2)+constant
The answer is:
xy(x+2)+constant
The answer (Indefinite)
[src]
/
|
| / 2 \ 2
| \x + y + 2*x - y/ dy = C + y*x + 2*x*y
|
/
∫((2x−y)+(x2+y))dy=C+x2y+2xy
2 / 2 \
x + 2*x - a*b*\x + 2*x/
−ab(x2+2x)+x2+2x
=
2 / 2 \
x + 2*x - a*b*\x + 2*x/
−ab(x2+2x)+x2+2x
x^2 + 2*x - a*b*(x^2 + 2*x)
Use the examples entering the upper and lower limits of integration.